Dialogue Discourse and Ideology of Popular Superstition: The Omani short story as a model - Al-Jadidi, Salim Nasir Salim (Journal of Humanities & Social Sciences, 2022)
The narrative prospective take many ways according to critical and literary practices devoted to it. So a group of narrative prospectives are formed not one as with John Boyon, Todrof, Girar Jenit but the soviet, ospesinki who made it on four levels, verbal, ideological, place and time psychological, from here, the essay aimed to showing one of these prospectives, which the researcher takes as problem of his research article it is the ideological prospective in narration, as a preient one in the verbal speech of characters as in the short Omani story as model. As this prospective, in my belief, is an ignored prospective – study and researcher – It was not given the due interest. especially as resulted in discourse speech (dialogue). The research reading of this prospective resulted in curriculum taking its sources of structural narrative approach. It is based on following ideological vision of present popular superstition in the dialogue between the short story characters in different times and stages in which the researcher thinks it takes a growing course and present a complete picture beginning from the seventieth and reaching in twenty first century. The essay treated clips of six Omani narrative stories, in which he thought of the ability of conversational discourse of showing the domination of this type of thought and what can be taken of deep and mysterious evidences, they may take a strange direction and obliteration of scientific and religions facts.